„Cały świat – samo życie”. Rola materii w malarstwie Tadeusza Kantora w latach 1945–1964 - Cieślak, Jan Piotr; Kozioł, Wiktoria; Kunińska, Magdalena (Artium Quaestiones, 2019)
The topic of the paper is the idea of matter in Tadeusz Kantor’s painting after World War II, including metaphorical painting, the informel, and the painting of the matter (1945-1964). The artist defined matter as an indeterminate, universal foundation which is a vehicle of the attributes of all that can be perceived by the senses, both animate bodies and inanimate things. A starting point are Kantor’s own texts – his notes and publications reflecting particular stages of his artistic evolution, critical essays on art, as well as later statements referring to the period under scrutiny. The present analysis is an attempt to find out whether Kantor’s postulates were really reflected in his art. Its main goal is to reconstruct his line of reasoning concerning matter and focus on the activities rooted in his theories, which is why contemporary reception and interpretations of his painting have not been taken into account. The frame of reference includes philosophical and artistic ideas known to Kantor or available to the artistic circles of the period. The text has been divided into four parts corresponding to particular stages of the artist’s development: (1) 1945-1947, when Kantor was trying to find ways of artistic expression beyond traditional topics of painting, such as the human figure, (2) 1947-1954, the metaphorical period, when, as a result of his visit to the Palais de la Découverte, he tried to represent the world invisible to the eye, (3) 1955-1959, the informelperiod, when paint became for him an equivalent of the matter, a synecdoche, one substance symbolizing all of it, and (4) 1958-1964, painting of the matter, when he kept using also other substances added to paint and chose a “concrete” approach to the painting’s meaning. The authors argue that over the first two decades following World War II Kantor succeeded in creating a new kind of painting, corresponding to the present, in which matter was to be dominant. To achieve that goal, for many years he was experimenting with different ways of representing matter – its ruling forces and principles. His initial existential observations, which challenged the uniqueness of humans in the universe, were later supplemented by shocking contact with science at the Paris Museum of Inventions. In the next decade, Kantor stopped making references to science and accepted process as a basic method of reaching the ontological foundation of the world, i.e. “matter.” His art was no longer “production,” but turned into “action.” At the last stage under consideration, he decided that the painting must not present signs referring to reality beyond it. He rejected the idea of painting as illusion and mediation, claiming that the matter of art is concrete, that it becomes “what it is.”